Case Report: Cardiac Involvement by Lymphoma: Rare but Heterogeneous Condition With Challenging Behaviors - Lucchini, Elisa; Merlo, Marco; Ballerini, Mario; Porcari, Aldostefano; Sinagra, Gianfranco; Pagnan, Lorenzo; Rensi, Marco; Romano, Andrea; Bussani, Rossana; Ballotta, Laura; Zaja, Francesco (Frontiers in Oncology, 2021)
Cardiac lymphomas are rare extranodal lymphomas involving primarily and secondarily the heart and/or pericardium. Here we describe three cases of cardiac involvement from lymphoma with specific peculiarities: two primary cardiac Diffuse Large B-cell Lymphoma and one secondary involvement from Marginal Zone Lymphoma (MZL). The first case highlights the issue of early CNS relapse and the possible role for CNS prophylaxis; the second case demonstrates the difficulties of interpretation and possible mistakes of different radiologic techniques adopted to evaluate cardiac involvement by lymphoma during follow-up; the third is a unique case of MZL with cardiac involvement. Our aim is to share the findings observed in these cases putting them in relation with data from the literature.